Una aproximación al desarrollo rural de Costa Rica. La extensión agrícola: breve síntesis de su evolución y tendencias hacia su democratización - Fernando Rivera-R (Universidad Nacional, Costa Rica, 2002)
In Costa Rica, agrarian outreach programs have been an important instrument for rural development. This study presents a valuable set of characteristics of the programs carried out since the 19 th century, and points out achievements related to the development models existing at different times in the institutional history of this country. From this perspective of agrarian outreach, and in particular, of the characteristics that it has since the 1990s, the author has proposed six lines of action for rural development. They include the democratization of outreach programs and a new approach toward research and agrarian outreach, oriented toward small and medium farmers.